Formulation And Permeability Studies Of Ritonavir: In Vitro Release And Caco-2 Cell Transport Analysis (The Review of Diabetic Studies, 2025)
The study aimed to enhance the oral bioavailability of Ritonavir (RTV), a poorly soluble HIV protease inhibitor, by formulating polymeric micelles using the biodegradable copolymer poly(ethylene glycol)-b-poly(ε-caprolactone) (PEG-PCL). A 3² factorial design was employed to optimize the formulation by evaluating the effects of drug-to-polymer ratio (X₁) and sonication time (X₂) on particle size (Y₁) and encapsulation efficiency (Y₂). The optimized RTV-loaded polymeric micelles (RTV-PMs) exhibited a mean particle size of 95.6 ± 4.1 nm, a polydispersity index of 0.18 ± 0.02, and an encapsulation efficiency of 92.4 ± 3.5%. Transmission electron microscopy confirmed their spherical morphology and uniform distribution. The in vitro release profile demonstrated a biphasic pattern with an initial burst followed by sustained release, achieving 85% cumulative release within 48 hours. Caco-2 cell permeability studies showed a 4.7-fold increase in apparent permeability (Papp) compared to pure RTV, indicating improved intestinal transport. In vivo pharmacokinetic evaluation in rats revealed a 3.8-fold enhancement in oral bioavailability without gastrointestinal toxicity. The findings suggest that PEG-PCL-based polymeric micelles provide a promising, scalable, and biocompatible platform for improving the solubility, permeability, and therapeutic performance of Ritonavir in antiretroviral therapy.